Cis-Effects Condition the Induction of a Major Unfolded Protein Response Factor, ZmbZIP60, in Response to Heat Stress in Maize - Li, Zhaoxia; Srivastava, Renu; Tang, Jie; Zheng, Zihao; Howell, Stephen H. (Frontiers in Plant Science, 2018)
Adverse environmental conditions such as heat and salt stress create endoplasmic reticulum (ER) stress in maize and set off the unfolded protein response (UPR). A key feature of the UPR is the upregulation of ZmbZIP60 and the splicing of its messenger RNA. We conducted an association analysis of a recombinant inbred line (RIL) derived from a cross of a tropical founder line, CML52 with a standard temperate line, B73. We found a major QTL conditioning heat-induced ZmbZIP60 expression located cis to the gene. Based on the premise that the QTL might be associated with the ZmbZIP60 promoter, we evaluated various maize inbred lines for their ability to upregulate the expression of ZmbZIP60 in response to heat stress. In general, tropical lines with promoter regions similar to CML52 were more robust in upregulating ZmbZIP60 in response to heat stress. This finding was confirmed by comparing the strength of the B73 and CML52 ZmbZIP60 promoters in transient maize protoplast assays. We concluded that the upstream region of ZmbZIP60 is important in conditioning the response to heat stress and was under selection in maize when adapted to different environments.